Feeding Cannabidiol (CBD)-Containing Treats Did Not Affect Canine Daily Voluntary Activity - Morris, Elizabeth M.; Kitts-Morgan, Susanna E.; Spangler, Dawn M.; Gebert, Jessica; Vanzant, Eric S.; McLeod, Kyle R.; Harmon, David L. (Frontiers in Veterinary Science, 2021)
Growing public interest in the use of Cannabidiol (CBD) for companion animals has amplified the need to elucidate potential impacts. The purpose of this investigation was to determine the influence of CBD on the daily activity of adult dogs. Twenty-four dogs (18.0 ± 3.4kg) were utilized in a randomized complete block design with treatments consisting of 0, 2 mg, and 4 mg CBD/kg BW/d split between two treats administered after twice-daily exercise (0700-0900 and 1700-1900). Four hours each day (1000-1200, AM and 1330-1530, PM), were designated as a time when no persons entered the kennels, with 2h designated as Quiet Time and the other 2h as Music Time, where calming music played over speakers. Quiet and Music sessions were randomly allotted to daily AM or PM times. Activity monitors were fitted to dogs’ collars for continuous collection of activity data. Data were collected over a 14-d baseline period to establish activity patterns and block dogs by activity level (high or low) before randomly assigning dogs within each block to treatments. After 7 d of treatment acclimation, activity data were collected for 14 d. Data were examined for differences using the MIXED procedure in SAS including effects of treatment, day, session (Quiet or Music), time of day (AM or PM), and accompanying interactions. CBD did not alter total daily activity points (P=0.985) or activity duration (P=0.882). CBD tended (P=0.071) to reduce total daily scratching compared with control. Dogs were more active in PM sessions than AM sessions (P<0.001). During the PM session, dogs receiving 4 mg CBD/kg BW/d tended (P=0.091) to be less active than control. During AM and PM sessions, CBD reduced scratching compared with CON (P=0.030). CBD did not affect activity duration during exercise periods (P=0.143). These results indicate that when supplemented with up to 4 mg CBD/kg BW/d, CBD does not impact the daily activity of adult dogs but may exert an antipruritic effect.